Effect of dragon fruit on glycemic control in prediabetes and type 2 diabetes: A systematic review and meta-analysis. - Nalinee Poolsup; Naeti Suksomboon; Naw Juna Paw (PLoS ONE, 2017)
Objective The purpose of this study was to systematically determine the effect of dragon fruit on glycemic control in prediabetes and type 2 diabetes. Methods Electronic databases including MEDLINE, CENTRAL, CINAHL, Scopus, ScienceDirect®, Proquest, Web of Science®, LILACS, NAPRALERT, SciFinder, Clinicalkey, Herbmed, NCCIH and Google Scholar were searched from their earliest inception up to March 2017 for relevant randomized controlled trials (RCTs) which compared dragon fruit with placebo or no treatment in prediabetes or type 2 diabetes. Clinicaltrials.gov, clinicaltrialresults.org, and ISRCTN registry were also searched. Personal contact with experts and historical search of related articles was undertaken. Outcome of interest were fasting plasma glucose (FPG) and 2 hours post-prandial glucose (2HPP). Study selection, data extraction and study quality assessment were performed independently by two investigators. Disagreements were resolved by a third reviewer. Treatment effect was estimated with mean difference (MD). Effect estimates were pooled using inverse-variance weighted method. Heterogeneity was assessed with the Q statistic and quantified with the I2 statistic. DerSimonian and Laird random-effects model was used when the Q-statistic was significant at the level of 0.1, otherwise a fixed-effects model was used. Results Among 401 studies identified from literature search, 4 RCTs involving 36 prediabetes subjects and 109 type 2 diabetes patients were included in the analysis. In prediabetes, FPG reduction was significant with MD of -15.1 mg/dL (95% CI: -23.8 to -6.5 mg/dL, P-value = 0.0006). Meta-analysis in type 2 diabetes showed no effect of dragon fruit on FPG (MD -26.5 mg/dL, 95% CI: -72.6 mg/dL to 19.6 mg/dL) and in 2HPP (MD -30.5 mg/dL, 95% CI: -80.9 mg/dL to 19.9 mg/dL). Conclusion The available evidence in prediabetes is interesting. This will shed some light on diabetes prevention. The effect in T2DM was not significant. However, a trend towards greater blood glucose reduction with higher dose was observed.